2005
DOI: 10.1002/mabi.200500150
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Novel Bone Scaffolds Based on Electrospun Polycaprolactone Fibers Filled with Nanoparticles

Abstract: Novel bone-scaffolding materials were successfully fabricated by electrospinning from polycaprolactone (PCL) solutions containing nanoparticles of calcium carbonate (CaCO(3)) or hydroxyapatite (HA). The diameters of the as-spun fibers were found to increase with the addition and increasing amounts of the nanoparticles. The observed increase in the diameters of the as-spun fibers with the addition and increasing amounts of the nanoparticulate fillers was responsible for the observed increase in the tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(145 citation statements)
references
References 22 publications
7
129
0
Order By: Relevance
“…The mean fiber diameters of the PCLrich and nHA-rich side of the meshes were calculated as 361±9 nm and 459±21 nm, respectively. A similar effect of nanoparticle inclusion on fiber diameter was also reported by other investigators [5,21]. The reason for increased fiber diameter could be partly explained by the presence of agglomerates of nHA.…”
Section: Fiber Diameter and Surface Propertiessupporting
confidence: 87%
“…The mean fiber diameters of the PCLrich and nHA-rich side of the meshes were calculated as 361±9 nm and 459±21 nm, respectively. A similar effect of nanoparticle inclusion on fiber diameter was also reported by other investigators [5,21]. The reason for increased fiber diameter could be partly explained by the presence of agglomerates of nHA.…”
Section: Fiber Diameter and Surface Propertiessupporting
confidence: 87%
“…The electrospun fibrous composites could be fabricated through blending polymer with nanoparticles or immobilization technologies to functionalize the electrospun nanofibers. For example, Wutticharoenmongkol et al [45] prepared electrospun PCL/hydroxyapatite (HA) and PCL/CaCO 3 composites using PCL solution containing nanoparticles of HA or calcium carbonate. Chang et al fabricated BG nanofibers by sol-gel electrospinning technology.…”
Section: Electrospun Fibrous Of Composite Scaffoldsmentioning
confidence: 99%
“…In vitro release study indicated that threads made from the core-shell fibers could suppress the initial burst release and provide a sustained drug release useful for administering growth factor or other therapeutic drugs. Yang et al obtained core-shell structured ultrafine fibers of BSA/PDLLA through emulsion electrospinning [45]. They found that emulsion electrospinning can provide a useful core-shell structure, which may serve as a promising scaffold for sustainable, controllable, and effective release of bioactive proteins for tissue engineering and other applications.…”
Section: Application Of Electrospun Fibers In Drug Deliverymentioning
confidence: 99%
“…Electrospinning of nHA/PCL using acetone solvent is not frequently reported and utilized. Common solvents that have been used to dissolve PCL for fabricating PCL nanofiber are dichloromethane/dimethyl formamide (Wutticharoenmongkol et al 2006), trifluoroethanol (Samavedi et al 2011), methanol/chloroform (Zhang et al 2007), methylene chloride/dimethyl formamide (Li et al 2012), and hexafluoroethanol (Jaiswal et al 2013). Some of these solvents are harmful and required attentive caution and safety precautions while preparing the solution for electrospinning.…”
Section: Introductionmentioning
confidence: 99%